PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVIMENT DIVISION ) UNTUK MENINGKATKAN KETERAMPILAN KERJA SAMA SISWA SEKOLAH DASAR - Aisyah, Aisyah; Syahrul Rizal, Muhammad; Ananda, Rizki; Rahma Rani, Afriza; Fitra Surya, Yenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low level of student collaboration skills in social studies learning in the VB class at Insan Kamil Bangkinang Elementary School, Bangkinang District, Kampar Regency City. One solution to overcome this problem is to apply the STAD (Student Teams Achievement Division) type cooperative learning model. The aim of this research is to improve students' collaboration skills in social studies learning. The research method used by researchers is Classroom Action Research (PTK), which is carried out in two cycles, each cycle consisting of 2 meetings and 4 stages, namely planning, implementation, observation and reflection. The time of the research was carried out from May-June 2024. The subjects of this research were 17 class V B students, consisting of 13 boys and 4 girls. Data collection techniques include documentation and observation. This was before the action was taken, the student's cooperation ability was 35.29%. After taking action in cycle I it increased to 66.66%. Meanwhile in cycle II it increased to 94.11%. Thus, it can be concluded that using the STAD (Student Teams Achievement Division) type cooperative learning model can improve students' collaboration skills in social studies learning at SD Insan Kamil Bangkinang.